Landslide monitoring in the Colca Valley, Peru, combined effect of precipitation and earthquake on the Maca landslide kinematic - Bontemps, Noélie (2021)
The Maca landslide, located in the Colca Valley, in the Arequipa region is threatening the security of the village composed of around 800 inhabitants, the development of tourism in the Colca valley (160 000 tourists in 2009) and the pre-Inca heritages. The landslide real-time monitoring started in 2015 when 3 huts were built, 2 on the landslide and one on the rim the landslide, with continuous GPS and seismic measurements. Those data are also a key to study the combined effect of earthquakes and precipitations on the landslide kinematics. Preliminary results showing the response of the landslide to 2 major earthquakes are shown, and hypothesis regarding the associated mechanics are presented in this study.